Questions: Given the explicit formula below, write the recursive formula for the sequence.
a(n)=11(-4)^(n-1)
Transcript text: Given the explicit formula below, write the recursive formula for the sequence.
\[
a(n)=11(-4)^{n-1}
\]
Solution
Solution Steps
To convert the given explicit formula to a recursive formula, we need to express the \( n \)-th term of the sequence in terms of the previous term(s).
For the given explicit formula \( a(n) = 11(-4)^{n-1} \):
Identify the first term \( a(1) \).
Determine the common ratio or difference between consecutive terms.
Formulate the recursive relation using the identified first term and the common ratio or difference.
Solution Approach
The first term \( a(1) \) can be found by substituting \( n = 1 \) into the explicit formula.
The common ratio \( r \) can be found by dividing \( a(n+1) \) by \( a(n) \).
The recursive formula will be of the form \( a(n) = r \cdot a(n-1) \) with the initial condition \( a(1) \).
Step 1: Identify the First Term
To find the first term \( a(1) \) of the sequence, we substitute \( n = 1 \) into the explicit formula:
\[
a(1) = 11(-4)^{1-1} = 11(-4)^0 = 11 \cdot 1 = 11
\]
Step 2: Determine the Common Ratio
The common ratio \( r \) can be found by dividing \( a(n+1) \) by \( a(n) \). Using the explicit formula:
\[
a(n+1) = 11(-4)^{(n+1)-1} = 11(-4)^n
\]
\[
a(n) = 11(-4)^{n-1}
\]
\[
r = \frac{a(n+1)}{a(n)} = \frac{11(-4)^n}{11(-4)^{n-1}} = (-4)
\]
Step 3: Formulate the Recursive Relation
Using the first term \( a(1) = 11 \) and the common ratio \( r = -4 \), the recursive formula can be written as:
\[
a(n) = -4 \cdot a(n-1)
\]
with the initial condition:
\[
a(1) = 11
\]